The responsiveness of curricular programs of computer schools in Iloilo City to the needs of the different industries - Delgado, Stephanie; Secreto, Eleanor; Vargas, John Paul.; Velasquez, Jessie John. (2001)
Every year, thousands of students graduate from computer related courses hopeful to join the country's workforce, only to be disappointed that job opportunities are unavailable to them. The same case is much as true in Iloilo City where computer schools continue to grow in nmber as well as the graduates that cannot find work. The workforce is growing and the country is in the brink of industrialization and global competitiveness, yet there is a noted inverse relationship between the supply of labor and employment. This situation is in contrast with the international scenario wherein demand for services of IT professionals is soaring high as well as the salaries being offered. The international scene is experiencing a shortage of competent IT professionals and it is even expected to continue for a long period of time. In Iloilo City, the opposite is true, for here, IT professionals are unable to find employment from businesses and industries. We begin to ask the question of whether there is indeed a mismatch between the quality of computer graduates and the quality that businesses needed. We linked this question to the ability of computer schools to effectively train their students to effectively meet the demands of the industry that are in need of their services. These considerations thus led to the study " The Responsiveness of Curricular Programs of Computer Schools in Iloilo City to the Needs of the different Industries". This study aims to find out the responsiveness of the computer schools to meet the demands of businesses in Iloilo City for computer workers. Specifically, it aimed to address the following areas-the skills and level of competence that computer schools require of their prospective employees, the skills and level of competence provided by computer schools to their students, the variation in the degree of responsiveness of the curricular programs of computer schools to the requirements of each type of industry, and the variation in the degree of responsiveness between two-yer and four year curricular programs. The respondents in this study is composed of a random sample of businesses in Iloilo City employing computer graduates in their operations. For the purposes of the study we classified the respondent businesses as merchandising, service and banking and finance. This study was conducted from December to March 2001. This study used the descriptive method of research and the instrument used to gather data is in the form of questionnaires. A pilot testing was done to ensure the clarity, validity and consistency of the questionnaires. The results of the survey were analyzed using the mean and frequency count, the chi squared, ANOVA and the Kruskal-Wallis test. Using the statistical tools mentioned above, our findings could be summarized as follows; that the curricular programs of the computer schools are very much responsive to the needs of the different industries. The study has shown that the skills and level of competence possessed by computer graduates exceed the requirement of the industry. another notable finding of the study is that is proved that there is a significant difference between the quality of graduates produced by four-year course from two-year course. Businesses in Iloilo City much prefer graduates of four-year course from two-year courses. This findings was attributed to the fact that computer schools base their curricular programs on international standards and prepare their students in the field of information technology. students are therefore higly qualified for the it market and can handle job requirements effectively. Iloilo City, on the other hand is still on it growth stage of industrial and commercial progress and the wide use of omputers in business operations is not yet visible. These factors were assumed to be the cause of the mismatch between the supply and demand for IT workers in Iloilo City.
Research Paper (BA 200 - Business Research) -- [Iloilo City : UPV-CM], March 30, 2001.